Digital technologies for financial inclusion of smallholder farmers: Needs assessment in three states of India - Ceballos, Francisco; Kannan, Samyuktha; Singh, Vartika; Kramer, Berber (International Food Policy Research Institute, 2019)
Financial instruments such as savings, loans, and insurance are critical tools in managing risk for smallholder farmers across the developing world. Although smallholder farmers are disproportionately affected by adverse events, they are the least likely to have access to formal loans, insurance, or bank accounts, leaving them less prepared to manage weather and disaster risk. As the effects of climate change intensify, building resilience—the ability to mitigate, cope, and recover from shocks and stresses without compromising future welfare—is essential for reducing rural poverty and improving food and nutrition security.